2018
DOI: 10.2174/1874210601812010555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Time Intervals between Bleaching Procedures on Enamel Microhardness and Surface Roughness

Abstract: Background:Dental bleaching has been increasingly sought out to improve dental aesthetics, but it may cause changes in dental enamel.Objective: To assess the influence of different time intervals on bleaching gel applications with regard to the Microhardness (MH) and Surface Roughness (SR) on dental enamel.Material and Methods:Forty bovine incisors were randomly divided into two groups (G1 and G2) and both were bleached with 35% Hydrogen Peroxide (HP35) (n=20; G1: seven-day interval and G2: two-day interval). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Approximately one third of CP decomposes to HP, which is the active agent of bleaching ( 1 , 4 , 8 , 9 , 12 ). Peroxides are unsTable substances that, in contact with dental tissues and moisture, release free radicals such as oxygen ions, which have the ability to diffuse through enamel and dentin and cause the oxidation of pigmented molecules that cause the tooth structure to darken ( 4 , 6 , 8 , 11 - 14 ). Home-use bleaching agents have been widely used in recent years, but some patients do not want to use bleaching trays or wait a few weeks to see the results of the bleaching, so these patients seek the in-office bleaching treatment that has more immediate results ( 2 , 3 , 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one third of CP decomposes to HP, which is the active agent of bleaching ( 1 , 4 , 8 , 9 , 12 ). Peroxides are unsTable substances that, in contact with dental tissues and moisture, release free radicals such as oxygen ions, which have the ability to diffuse through enamel and dentin and cause the oxidation of pigmented molecules that cause the tooth structure to darken ( 4 , 6 , 8 , 11 - 14 ). Home-use bleaching agents have been widely used in recent years, but some patients do not want to use bleaching trays or wait a few weeks to see the results of the bleaching, so these patients seek the in-office bleaching treatment that has more immediate results ( 2 , 3 , 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching effectiveness as well as the changes caused on enamel surface and side effects depends mainly on relationship established between the concentration of gel and its time of use, and may also be influenced by diffusion capacity of bleaching agent and its pH ( 4 - 6 , 9 , 11 , 14 ). The pH can change not only the bleaching efficacy, but it can also reduce the hardness, increase the roughness and cause the wear of tooth enamel ( 6 , 13 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both properties had negative changes, drawing the attention to the large increase of roughness which directly interferes in the vitreous aspect of the enamel. The authors stated that the lower the saliva-enamel contact time between sessions (2 days), the lower the protective effect, which was visualized in the group with a 7-day interval 13 .…”
Section: G1 -Sevenmentioning
confidence: 99%
“…A study of 2015, evaluated the effect of decreasing interval's time between clinical bleaching sessions on the risk and intensity of tooth sensitivity, using 35% hydrogen peroxide (35% HP), and concluded that reduction of the interval from seven to two days had similar teeth whitening response and, also, reduced the treatment time without increasing the bleaching-induced tooth sensitivity 12 . Nonetheless, an in vitro study of 2018 found that the reduction in time interval between sessions to 2 days might cause a decrease in microhardness and augment in roughness 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation